a(3u-v)+a(u+2v)

asked by guest
on Jan 28, 2025 at 2:56 pm



You asked:

Evaluate the expression: a(3uv)+a(u+2v)a\left( 3 u - v \right) + a\left( u + 2 v \right)

MathBot Answer:

Evaluated



a(3uv)+a(u+2v)=a(3uv)+a(u+2v)\displaystyle a\left( 3 u - v \right) + a\left( u + 2 v \right) = a \left(3 u - v\right) + a \left(u + 2 v\right)


Expanded

a(3uv)+a(u+2v)=4ua+vaa\left( 3 u - v \right) + a\left( u + 2 v \right) = 4 u a + v a


Factored

a(3uv)+a(u+2v)=a(4u+v)a\left( 3 u - v \right) + a\left( u + 2 v \right) = a \left(4 u + v\right)